Examining some physical parameters of elite basketball players playing in different leagues - Yüksel, M. F. (Turkish Journal of Sport and Exercise, 2017)
Objective of this study is to examine some physical parameters of basketball players at elite level who are playing in different league levels. Total 24 sportsmen consisting of 12 sportsmen from Turkish Man Basketball 2nd League and 12 sportsmen from Turkey Men Basketball 3rd league whose training age is minimum 5, voluntarily participated to this study. Vertical jumping, 20 m speed running, hand grip strength (right and left), flexibility, 30 sec do sit-ups, 30 sec push-up, 20 m shuttle running tests were performed for determining physical properties of basketball players. It was determined that the 2nd league basketball players had better hand grip strength (right-left), Max VO2 and anaerobic power values than basketball players playing in the 3rd league. Statistically significant difference was determined in 20 m speed running parameter (p<0.05). It was also determined that vertical jump, flexibility, 30 sec do sit-ups and 30 sec do push-up values were similar in two groups. Similarity which is observed in values of male basketball players who play in both leagues can be explained with proximity at rivalry levels between leagues. This proximity at competition level which is observed between particularly 2nd and 3rd leagues are projected in physical profiles of players. In addition to this differences which are seen in some parameters may be caused from differences in training programs. It is considered that technical, tactical and psychological properties of players are important for determining players between leagues in addition to physical properties.